2-(4-Methoxyphenyl)ethyl-2-acetamido-2-deoxy-β-D-pyranoside, an analog of salidroside, contributes to neuroprotection in cerebral ischemic injury in vitro and in vivo. Issue 5 (21st March 2018) - Yu, Shu; Wei, Li; Chi, Xiaojing; Xu, Hui; Ding, Fei
Abstract : 2-(4-Methoxyphenyl)ethyl-2-acetamido-2-deoxyb-D-pyranoside (code-named SalA-4g), an analog of salidroside, has potent neuroprotective effects. In this study, the pharmacological properties of SalA-4g were evaluated in primary cortical neurons exposed to oxygen and glucose deprivation and in a rat model of transient middle cerebral artery occlusion. The results of pharmacokinetic and brain distribution studies indicated that SalA-4g could pass through the blood–brain barrier with a relatively short elimination time. 3-[4, 5-Dimethyl-2-thiazolyl]-2, 5-diphenyl tetrazolium bromide assay, terminal deoxynucleotidyl transferase dUTP nick-end labeling, and Annexin V staining collectively showed that SalA-4g inhibited neuronal viability loss and apoptosis in a concentration-dependent manner in an oxygen and glucose deprivation model. Fluorine-18-fluorodeoxyglucose PET/CT imaging indicated that SalA-4g improved metabolic recovery in the ischemic hemisphere in a rat middle cerebral artery occlusion model. Our findings provide further evidence of the potential therapeutic applications of SalA-4g for the treatment of cerebral ischemic injury.